The Value of Cytology Smears for Acanthamoeba Keratitis - Sangita P. Patel; Jamie L. Schaefer; Ryan Jaber; Joyce Paterson; Weiguo Liu; Federico Gonzalez-Fernandez (Case Reports in Ophthalmological Medicine)
Purpose. Acanthamoeba keratitis remains a difficult diagnosis despite advances in genetic and imaging technologies. The purpose of this paper is to highlight the utility of cytology smears for diagnosis of Acanthamoeba keratitis. Methods. This is a case study of the diagnostic course for a patient with suspected Acanthamoeba keratitis. Results. A 40-year-old male with poor contact lens hygiene presented with severe left eye pain. Slit lamp examination showed two peripheral ring infiltrates without an epithelial defect. The epithelium over both infiltrates was removed with a Kimura spatula. Half of the sample was smeared on a dry microscope slide and the other half was submitted for Acanthamoeba culture and PCR. Both culture and PCR were negative for Acanthamoeba, but hematoxylin and eosin stain of the smear revealed double-walled cysts. Conclusion. H&E staining of corneal cytology specimens is an efficient and readily available test for diagnosis of Acanthamoeba keratitis.